Holograms and Virtual Sculpture: A Study in the Physical Vanishing of Digital Sculptures Works by artist Paula Dawson (as a model) - Essam Nazar Mohammad Jawad ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
This research examines the radical transformations witnessed in the art of sculpture as a result of rapid technological advancements. Techniques such as holography and virtual sculpting have reformulated the foundational concepts of this art form, transcending the traditional boundaries of materiality toward digital realms reliant on light and information rather than tangible materials. The study focuses on the artistic and technical aspects of these modern technologies, exploring their impact on the interaction between the artist and the audience, as well as the philosophical and aesthetic challenges that have emerged with the diminishing presence of the physical element in digital sculptural works.The research seeks to investigate whether sculpture can retain its creative essence despite its shift into an immaterial form. It explores the emerging relationship between physical reality and digital representations, which has opened the door to new sculptural methods that surpass traditional constraints such as size, weight, and space. Additionally, it addresses the effects of these changes on the audience’s experience, particularly with the disappearance of direct sensory interaction—such as touch and the perception of texture—which was a fundamental component of traditional sculpture, replaced instead by visual engagement in holographic and virtual works.The study delves deeply into the visual perception of holographic sculpture, which relies primarily on light, posing new challenges regarding how these works are received and interpreted in the absence of a physical experience. Simultaneously, it highlights the capacity of digital technology to create dynamic and interactive sculptural experiences, enabling the design of works that evolve based on the viewer’s movements or adapt to diverse virtual environments.On another level, the research discusses how these technologies necessitate a reevaluation of concepts of beauty and art. Digital sculpture demands the formulation of new aesthetic standards suited to its intangible nature, while also anticipating the role of artificial intelligence in enhancing sculptural creativity through innovative approaches to handling digital materials.Through a critical analysis of these developments, the research concludes that digital and holographic sculpture is not merely an evolution of traditional sculpture but rather an independent art form with distinct characteristics reflective of the digital age. It sheds light on future challenges, whether in terms of techniques, modes of interaction, or the place of this art within the contemporary visual landscape. In its conclusion, the study proposes pathways to enhance the audience’s experience by advancing virtual and augmented reality technologies, creating immersive environments that reshape the relationship between the artist and the public amid the ongoing digital revolution.DOI: https://doi.org/10.54633/2333-024-056-015